Population dynamics and genetic structure of Wallago attu (Bloch & Schneider,1801) from the Confluent Rivers of Vembanad Lake,Kerala,India - Thella Rufus (KUFOS, 2016)
Abstract- The Asian silurid catfish Wallago attu is one of the fastest growing catfish having high nutritional value and market demand. It is also one of the heavily exploited riverine catfish in Kerala. A study was conducted to understand the population and genetic characteristics of Wallago attu from the confluent rivers of Vembanad Lake. The length weight relationship revealed b values from 2.7 to 3.5 and K value less than one. Length frequency analysis showed that all population except Parumala are more or less under exploitation pressure and the populations at Changanassery was overexploited. Genetic variations between Wallago attu populations collected from different rivers draining the Vembanad Lake as well as from other sites across India revealed that there is no noticeable genetic structuring of the populations.